Immunohistochemical study of the endocrine cells in the stomach and pyloric caeca of the mountain trout, Salmo trutta macrostigma - Tarakci, Gencer B.; Bayrakdar, A.; Yaman, M. (Iranian Fisheries Research Organization, 2012)
The endocrine cells of Salmo trutta macrostigma stomach and pyloric caeca have been investigated using immunohistochemical techniques. 8 antisera were tested and 6 of them were detected in the endocrine cells; serotonin, somatostatin, substance P, galanin, CCK and neuropeptide Y. These immunoreactive cells are described for the first time in the stomach and pyloric caeaca of Salmo trutta macrostigma. Neurotensin and VIP immunoreactivity were not detected in these regions. The regional distribution and relative frequency of the endocrine cells in the stomach and pyloric caeca of Salmo trutta macrostigma were resembled (with respect to serotonin, somatostatin, CCK and substance P immunoreactivity) and showed also some particularities (presence of galanin and NPY positive cells) to those of the other salmonid species.
Keywords: Endocrine cell; Stomach; Pyloric caeca; Salmo trutta macrostigma; Immunohistochemistry